ORGANIZATIONAL CLIMATE AND EMPLOYEES’ COMMITMENT: EVIDENCE FROM MANUFACTURING INDUSTRY - Ibrahim Yinka AGBEYINKA (International Journal of Social and Educational Innovation)
Organizational climate is the core circle of human environment within the boundaries of where the employees in an organization work. Further explained that climate affects every activity in an organization directly or indirectly and is affected by almost everything that happens in the organization. The survival and growth of any organization is directly affected by a favorable climate. Literature suggests that positive work-related behaviour and attitudes largely depends on employee perceptions on the extent to which their employer values their contribution and cares about their wellbeing The study aims to investigate the organizational climate and employees’ commitment. The study seeks three specific objectives, including to determine the impact of job autonomy on employee morale; to ascertain the effect of a leadership style on the employee productivity and to establish relationship between reward system and employee job satisfaction. The paper is guided by three following null hypotheses. The first hypothesis (H1) assumes that job autonomy does not have impact on employee morale. The second hypothesis (H2) assumes that leadership style does not influence the employee productivity, and the third hypothesis (H3) assumes that there is no relationship between reward system and employee job satisfaction. The findings apparently show that passionate employee will contribute more efficiently towards the growth of the organisation. The organisation’s work climate has significant effect on employee commitment in the manufacturing company. The variables such as autonomy, leadership style, reward system and opportunities for growth instill passion in employees to be more productive. The implication here is that favourable organisational climate or work environment will enable an enhanced efficiency in production.